PENGEMBANGAN MEDIA PEMBELAJARAN INTERAKTIF BIG BLUE BUTTON PADA MATAKULIAH STRUKTUR DATA (Teknosia, 2023)
The development of the Big Blue Button interactive learning media in the Data Structures course is an innovative step in the world of education. The aim of this research is to increase student learning effectiveness in understanding basic concepts in the Data Structures course. This research focuses on the design and development of Big Blue Button-based learning media with various interactive features contained in it. The main aim of this research is to create a learning environment that supports discussion, interaction, presentation and collaboration between lecturers and students. The research methods used include requirements analysis, interface design, development and testing. The research results show that the use of the Big Blue Button in the Data Structures course can improve the quality of learning, increase student participation, and make it easier to access learning materials. In addition, educational institutions can utilize web conferencing technology to enrich student learning experiences. This research is expected to have the potential to provide significant benefits in distance learning, especially in the context of learning programming techniques. By using this technology students can gain a more interactive and collaborative learning experience in understanding data structure concepts. Keyword: Interactive Learning Media, Big Blue Buttons, Data Structures